Remodelling hierarchical NiCo2O4@ZnS nanorods with multi-walled carbon nanotubes as a counter electrode for dye-sensitized solar cell applications - Nukunudompanich, Methawee; Nachaithong, Theeranuch; Phumuen, Phatcharin; Wannabut, Wassana; Kunbuala, Neeraphat; Nijpanich, Supinya; Pattarith, Kongsak; Areerob, Yonrapach (My University, 2026)
A hierarchical NiCo2O4@ZnS/MWCNT (NCO@Z-MWCNTs) nanocomposite was synthesized to serve as a platinum-free counter electrode for dye-sensitized solar cells (DSSCs). The nanocomposite comprised spinel NiCo2O4 nanorods, ZnS associated with the surface of the nanorods, and an interconnected multi-walled carbon nanotube (MWCNT) network, and it was synthesized via a low-temperature solution-based hydrothermal method. XRD confirmed the presence of cubic NiCo2O4 and zinc blende ZnS phases, while FESEM–EDS and XPS analyses verified the incorporation of ZnS and the formation of a conductive carbon framework interconnecting adjacent nanorods. ZnS, rather than acting as an isolated catalytic component, was considered to contribute additional sulfide-related surface sites and to modulate the interfacial electronic environment of the NiCo2O4 nanorods, which likely facilitated redox reactions involving the I−/I3− couple. Meanwhile, the MWCNT network established continuous electron transport pathways, effectively reducing interfacial resistance and enhancing charge-transfer efficiency. Thermogravimetric and electrochemical analyses revealed enhanced thermal stability, improved redox kinetics, and a significant reduction in charge-transfer resistance compared with pristine NiCo2O4.The optimized NCO@Z–MWCNT 9wt% counter electrode achieved a power conversion efficiency of 10.03% under AM 1.5 G illumination, exceeding that of the Pt reference device (9.6%). Overall, the improved performance was attributed to the combined contributions of ZnS surface modification and the conductive MWCNT network, which together enhanced charge transport and electrocatalytic activity. This work demonstrates a scalable strategy for developing cost-effective, durable, and high-performance counter electrodes for dye-sensitized solar cells.
Keywords: Counter electrodes; Dye-sensitized solar cells; NiCo2O4@ZnS/MWCNT nanocomposite